2007
DOI: 10.1002/ca.20524
|View full text |Cite
|
Sign up to set email alerts
|

Protective intercoronary continuity

Abstract: Intercoronary continuity, a congenital open-ended continuity with bidirectional blood flow between two major epicardial coronary arteries, is a rare variation in the coronary anatomy. It has been speculated by Esente et al. (1983) that such type of open-ended circulation may prevent the development of myocardial infarction if severe obstruction of one of the coronary arteries develops, but this has never been reported. A 48-year-old male suffered chest pain suggestive of acute myocardial infarction. The 12-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…However, this large anastomotic connection might have a potential role in protecting the myocardium in the presence of significant stenosis in either of the parent arteries. 3,4 To support this hypothesis, our case had totally occluded LAD and severe stenosis in the proximal RCA, but she was hemodynamically stabile and could survive. Moreover, despite the significant stenosis in the proximal RCA, inferior ischemia was not detected during the myocardial perfusion.…”
Section: Introductionmentioning
confidence: 69%
“…However, this large anastomotic connection might have a potential role in protecting the myocardium in the presence of significant stenosis in either of the parent arteries. 3,4 To support this hypothesis, our case had totally occluded LAD and severe stenosis in the proximal RCA, but she was hemodynamically stabile and could survive. Moreover, despite the significant stenosis in the proximal RCA, inferior ischemia was not detected during the myocardial perfusion.…”
Section: Introductionmentioning
confidence: 69%
“…Intercoronary continuity is a congenital open-ended connection with bidirectional flow between two major epicardial coronary arteries. [2] Atak et al [3] and Arat-Ozkan et al [4] reported their individual cases among 7,086 and 12,674 angiograms, respectively. In a postmortem study of 100 human hearts, it was detected in seven cases.…”
Section: Case Reportmentioning
confidence: 99%
“…[6] Intercoronary connection is a single straight epicardial vessel with a diameter of ≥1 mm and composed of layers of a typical muscular artery, connecting the terminal portions of major epicardial vessels. [2] Although some authors speculated that these connections may have a potential protective role in the myocardium against obstructive CAD, [1] their functional significance remains unclear. Our case of inter-coronary continuity was associated with myocardial ischemia, which we think is the first reported feature in the literature.…”
Section: Case Reportmentioning
confidence: 99%